2017
DOI: 10.1097/lbr.0000000000000333
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy Safety in Patients With Chronic Obstructive Lung Disease

Abstract: Bronchoscopy is generally safe with few complications in most patients with COPD. Patients with objectively confirmed severe to very severe COPD had more frequent respiratory complications than patients without COPD. The risks were not prohibitively high, but should be taken into consideration for COPD patients undergoing moderate sedation flexible bronchoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
2
23
2
Order By: Relevance
“…The only statistically significant difference between COPD subjects and controls was more postprocedural dyspnoea in COPD subjects. These findings are in accordance with a recent study that reported similar safety profiles in patients with and without COPD,15 and previous findings of more respiratory complications in COPD patients following bronchoscopy 16. Predictors of unplanned intervention or early procedure termination were lack of sedation and higher age.…”
Section: Discussionsupporting
confidence: 92%
“…The only statistically significant difference between COPD subjects and controls was more postprocedural dyspnoea in COPD subjects. These findings are in accordance with a recent study that reported similar safety profiles in patients with and without COPD,15 and previous findings of more respiratory complications in COPD patients following bronchoscopy 16. Predictors of unplanned intervention or early procedure termination were lack of sedation and higher age.…”
Section: Discussionsupporting
confidence: 92%
“…Obtaining AM by BAL can be difficult in severe COPD or during exacerbations because of increased risk of bronchoscopy (45). This study is the first to show a correlation between phagocytic capacity in paired AM and MDM ( Figure 5), suggesting MDM could be used as a model of AM phagocytosis.…”
Section: Discussionmentioning
confidence: 67%
“…Patients with COPD and chronic kidney disease showed an increased risk of experiencing cardiopulmonary events during a bronchoscopy. While bronchoscopy is generally safe in most patients with COPD 27 , patients with severe to very severe COPD could have more frequent respiratory complications than patients without COPD 28 . In addition, OSA coexisting with COPD, called COPD-OSA overlap syndrome 29 , might affect the risk of cardiopulmonary events occurring during bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%